Systematic revision of the family Hoplitomerycidae Leinders, 1984 (Artiodactyla: Cervoidea), with the description of a new genus and four new species - van Der Geer, Alexandra A. E. (Zootaxa, 2014)
Six species of the cervoid genus Hoplitomeryx are currently recognized from the Late Miocene sites of Gargano and Scontrone, in Italy: H. matthei Leinders, 1984, H. apruthiensis Mazza & Rustioni, 2011, H. apulicus Mazza & Rustioni, 2011, H. falcidens Mazza & Rustioni, 2011, H. magnus Mazza & Rustioni, 2011, and H. minutus Mazza & Rustioni, 2011. These species are interpreted as members of an anagenetic series in these two localities, which are considered as part of the same bioprovince but with different geological ages. Comparative analysis of postcranial, dental, and cranial material from Hoplitomerycidae resulted in the reinterpretation of this current taxonomic arrangement. Two distinct genera can be distinguished. The new genus Scontromeryx is restricted to Scontrone (Early Tortonian) and is characterised by the presence of second upper and lower premolars and the absence of a nasal (median) horn. Hoplitomeryx is restricted to Gargano (Middle and/or Late Tortonian), and is characterized by the loss of the second premolar and presence of a nasal horn. Both genera are characterized by orbital appendages in some species, but the morphology of these appendages differs between the genera. Six species can be recognized for Scontromeryx gen. n.: S. minutus (type species), S. falcidens, S. apulicus, S. apruthiensis, S. magnus (new combinations) and the newly described S. mazzai sp. n.. Hoplitomeryx is represented by the H. matthei (type species) and 3 newly described species H. devosi sp. n., H. macpheei sp. n. and H. kriegsmani sp. n.. These two multispecies assemblages are best explained as independent adaptive radiations with the two genera as sister taxa. There is no evidence that the two localities were connected during the Late Miocene.